A Reaction Time Experiment on Adult Attachment: The Development of a Measure for Neurophysiological Settings - Wichmann, Theresia; Buchheim, Anna; Menning, Hans; Schenk, Ingmar; George, Carol; Pokorny, Dan (Frontiers in Human Neuroscience, 2016)
In the last decades, there has been an increase of experimental research on automatic unconscious processes concerning the evaluation of the self and others. Previous research investigated implicit aspects of romantic attachment using self-report measures as explicit instruments for assessing attachment style. There is a lack of experimental procedures feasible for neurobiological settings. We developed a reaction time experiment (RT) using a narrative attachment measure with an implicit nature and were interested to capture automatic processes, when the individuals’ attachment system is activated. We aimed to combine attachment methodology with knowledge from implicit measures by using a decision reaction time paradigm. This should serve as a means to capture implicit aspects of attachment. This experiment evaluated participants’ response to prototypic attachment sentences in association with their own attachment classification, measured with the Adult Attachment Projective Picture System (AAP). First the AAP was administered as the standardized interview procedure to 30 healthy participants, which were classified into a secure or insecure group. In the following experimental session, both experimenter and participants were blind with respect to classifications. 128 prototypically secure or insecure sentences related to the 8 pictures of the AAP were presented to the participants. Their response and reaction times were recorded. Based on the response (accept, reject) a continuous security scale was defined. Both the AAP classification and security scale were related to the reaction times. Differentiated study hypotheses were confirmed for insecure sentences, which were accepted faster by participants from the insecure attachment group (or with lower security scale), and rejected faster by participants form secure attachment group (or with higher security scale). The elaborating unconscious processes were more activated by insecure sentences with potential attachment conflicts. The introduced paradigm is able to contribute to an experimental approach in attachment research. The Reaction Time analysis with the narrative procedure might be of interest for a broader variety of questions in experimental and neurophysiological settings to capture unconscious processes in association to internal working models of attachment. An electrophysiological model based on preliminary research is proposed for assessing the preconscious neuronal network related to secure or insecure attachment representations.